DEVELOPMENT OF CANVA LEARNING MEDIA IN INCREASING STUDENT SELF-EFFICACY AT MI AL ADNANI JOMBANG /تطوير الوسيلة التعليمية بتطبيفات "كنفا" في تنمية الكفاءة الذاتية لدي الطلاب في المدرسة الإبتدائية العدناني جومبانج - Qomariyah, Lailatul; Mulloh, Tamim; Fadhilah, Lailatul (Jurnal Al-Maqoyis, 2023)
This article discusses the professional competence of Arabic language teachers in six schools in the Central Kalimantan region which have not met according to the standards set by the Regulation of the Minister of National Education of the Republic of Indonesia Number 16 of 2007 concerning Academic Qualification Standards and Teacher Competency. This Research used the qualitative method by implementing phenomenological interviews. Through the results of the research, three Arabic teachers were found with inappropriate educational backgrounds. During the learning reflection process, the three Arabic teachers did many reflection activities to improve the quality of learning, such as evaluating learning, researching in the classroom, studying alone, observing themselves and students, attending training, being innovative, recording the learning process, analyzing students' needs, and meeting students' needs by analyzing them. The study suggests that Arabic teachers should regularly reflect to improve the quality of learning and meet professional competency standards.